Low-Density Lipoprotein Cholesterol and Alzheimer's Disease: A Systematic Review and Meta-Analysis - Zhou, Zhike; Liang, Yifan; Zhang, Xiaoqian; Xu, Junjie; Lin, Jueying; Zhang, Rongwei; Kang, Kexin; Liu, Chang; Zhao, Chuansheng; Zhao, Mei (Frontiers in Aging Neuroscience, 2020)
Objective: To assess the association between low-density lipoprotein cholesterol (LDL-c) and risk of Alzheimer's disease (AD). Methods: Embase, Pubmed, and Web of Science were searched until June 2019. Standard mean difference (SMD) with 95% confidence intervals (CI) was estimated using random-effects models. Results: Our meta-analysis of 26 studies revealed higher levels of LDL-c in AD than that of non-dementia controls (SMD = 0.35, 95% CI 0.12–0.58, p < 0.01). The meta-regression analysis on confounders showed that age (p < 0.01, Adj R-squared = 92.41%) and cardiovascular disease (p = 0.01, Adj R-squared = 85.21%), but not the body mass index, education, smoking, hypertension and diabetes mellitus, exerted an impact on the relationship between LDL-c and risk of ICH. Further subgroup analysis of age showed LDL-c levels in AD patients aged 60–70 were higher than that of non-dementia (60 ≤ age < 70: SMD = 0.80, 95% CI 0.23–1.37, p < 0.01); but no association between the SMD of AD in LDL-c and age over 70 was noted across the studies (70 ≤ age < 77: SMD = −0.02, 95% CI −0.39 0.34, p = 9.0; 77 ≤ age < 80: SMD = 0.15, 95% CI −0.17 0.47, p = 0.35; ≥80: SMD = 0.53, 95% CI −0.04 1.11, p = 0.07). The concentrations of LDL-c during the quintile interval of 3 4 were positively associated with AD (121 ≤ concentration < 137: SMD = 0.98, 95% CI 0.13 1.82, p = 0.02; ≥137: SMD = 0.62, 95% CI 0.18 1.06, p < 0.01); whereas there was no correlation between AD and LDL-c within the quintile interval of 1 2 (103.9 ≤ concentration < 112: SMD = 0.08, 95% CI −0.20 0.35, p = 0.59; 112 ≤ concentration < 121: SMD = −0.26, 95% CI −0.58 0.06, p = 0.11). Conclusions: Elevated concentration of LDL-c (>121 mg/dl) may be a potential risk factor for AD. This association is strong in patients aged 60–70 years, but vanishes with advancing age.